Chewing Function with Efficiency Tests in Subjects Wearing Clear Aligners - Luca Levrini; Alessandro Deppieri; Andrea Carganico; Giorgia Rodigari; Stefano Saran; Piero Antonio Zecca; Marco Cicciù; Salvatore Bocchieri (MDPI AG, 2024)
This study assessed the masticatory function of participants wearing clear aligners in order to determine whether these devices can be worn even when eating and therefore worn to extend treatment time and boost treatment effectiveness. An intercontrol test was conducted on 20 patients who received Invisalign® treatment. Each participant was instructed to chew two pieces of Hue-Check Gum® chewing gum (one pink and the other blue) in 5, 10, and 20 cycles both with and without aligners. After being removed from the oral cavity, the gum was dried and pressed using a 1 × 50 × 50 mm model that was 3D printed with a transparent layer in between. After being scanned on both sides with a flatbed scanner at 600 dpi, the samples were saved as jpg files and subjected to an optoelectronic examination using ViewGum software. To validate the procedure, a control group from a different institution (University of Bern) was used. A statistical analysis of the data was carried out. The Shapiro-Wilk test was used to confirm the normality of the samples. A one-way ANOVA test, a homogeneity of variance test, and a t-test did not reveal statistically significant differences between the two control groups, thus validating the methodology employed. In summary, clear aligners do not radically change the masticatory function while they are worn. As a result, clinicians can exploit the aligners for chewing to obtain a better fit of the plastic material to the dental surface and to attachments. Treatment times for patients could also be shorter.